The Effect of Local Government Size, Local Original Revenue (PAD), Balance Funds, Capital Expenditures, on Local Government Financial Performance - Zahrotul Mukaiyaroh; Sri Anik (Masyarakat Ekonomi Syariah Bogor, 2025)
This study aims to analyze the effect of local government size, regional own-source revenue (PAD), balancing funds, and capital expenditure on local government financial performance in districts / cities in Central Java Province in 2021-2023. The method used is quantitative with an explanatory research approach. Data were obtained through documentation of local government financial reports and analyzed using multiple linear regression. The results showed that local government size and PAD had a significant positive effect on financial performance. Meanwhile, balancing funds have a significant negative effect, while capital expenditure has no significant effect on regional financial performance. These findings indicate the importance of optimizing PAD and managing balancing funds efficiently as well as the role of government size in improving the effectiveness and efficiency of local finances. The implications of these results provide input for local governments in formulating fiscal policies that are accountable and oriented towards improving public services.